Potensi Tumbuhan Lemna minor L. sebagai Agen Fitoremediasi Limbah Cair Pewarna Jumputan - Erin Damayanti Hutabarat; Susy Amizera; Didi Jaya Santri (Universitas Sam Ratulangi, 2024)
Jumputan cloth is a type of typical cloth originating from the city of Palembang. In the manufacturing process it uses a lot of dyes so that it produces waste in the form of liquid dye waste. This research aims to determine the potential of the Lemna minor L. plant in reducing color levels and improving the quality of jumputan dye waste water. This research is a quantitative research with experimental methods using a Completely Randomized Design (CRD) with 5 treatments and 5 replications. Data analysis was carried out using the normality test, homogeneity test, variance test, and Duncan test. The research results showed that the Lemna minor plant was able to reduce color levels by 51%, and was able to improve water quality parameters, namely by changing the pH to 5.72 with a percentage of 18%, DO to 6.9 mg/l with a percentage of 53%, the temperature becomes 27.9°C with a percentage of 11%, TDS becomes 118.2 mg/l with a percentage of 44%, TSS becomes 8 mg/l with a percentage of 95%, and Pb metal becomes 0.9 with a percentage of 42%. Based on the research results, it can be concluded that the Lemna minor L. plant is effectively used as a phytoremediator for jumputan dye liquid waste.